Literary rendez-vous with Zdenek Rotrekl or A few remarks on Jiri Zizler's book The Aristocrat of the Catacombs - Sladek, Ondrej (Bohemica Olomucensia, 2023)
The main topic of the study is a critical consideration of the analytical and interpretative methods used by the literary historian and critic Jiri Zizler in his monograph on the poet Zdenek Rotrekl - The Aristocrat of the Catacombs. Towards the Life and Work of Zdenek Rotrekl (2021). The study demonstrates that Zizler's book is the result of the combination of several approaches: the literary-critical, historical, and comparative, as well as the structural, phenomenological, and hermeneutical. One must also add the method of close reading, which Zizler uses to create his interpretive models.
Keywords: Jiri Zizler; Zdenek Rotrekl; poetics; interpretation; Czech catholic literature.